Vitamin D status among female handball and football elite athletes in Norway at latitude 60°N - Jonvik, K. L. (2011)
An unexpectedly high prevalence of vitamin D insufficiency has recently been reported worldwide, but little is known about the level in athletes. Vitamin D has known skeletal functions with high impact on bone health. The vitamin also has muscle and immune functions and low levels have been linked to decreased muscle strength in elderly and chronic diseases. If these functions can affect an athlete`s health status and performance are yet to be established. Purpose: To measure serum vitamin D concentrations, as 25-hydroxyvitamin D (25(OH)D), in female elite athletes in handball and football in the south eastern parts of Norway, at latitude 60ºN. We also wanted to address possible exposure factors of the 25(OH)D level in this group, by investigating dietary intake, supplement use and sun behavior. Methods: Serum 25(OH)D concentrations were measured in 48 female elite athletes (26 handball/22 football) in October/November 2010. Insufficiency was defined as serum 25(OH)D concentration <80 nmol/l. Dietary intake was assessed with four-day weighed diet record. Supplement use and sun exposure were assessed via interviewer-assessed questionnaires. Results: Mean serum 25(OH)D level was 99 (SD=32) nmol/l. Vitamin D insufficiency was found in 27 percent of the subjects. Serum 25(OH)D levels were found to be significantly higher for the handball compared to the football players (p=0.001). The subjects residing only in Nordic countries in summer had a significantly lower 25(OH)D level than the subjects going outside of Nordic countries (p=0.039). The handball players resided significantly less in Nordic countries in summer than the football players (p=0.004). Seventy-three percent of all subjects had a vitamin D intake below the recommended intake of 7.5 µg/day. Conclusion: In this study, of female elite athletes living at high latitude, the average 25(OH)D level in fall was similar to optimal level, and vitamin D insufficiency was found in one out of four of the athletes. Going outside of Nordic countries in summer seemed to be the factor of most influence on the 25(OH)D levels. Since the subjects live at high latitude and since vitamin D intake was below recommendations for ¾ of the subjects, their 25(OH)D level is likely to decrease during winter. Hence, it needs to be debated if routine screening for 25(OH)D levels in female elite athletes should be recommended.